Schizophyllum Commune As Nano-Factory For Biosynthesis Of Silver Nanoparticles - Mat Don, Mashitah; Chan, Yen San (2011)

(untitled)
Silver nanoparticles (AgNPs), are the noble metal nanoparticles that are being studied extensively due to their antimicrobial properties[1].